Effect of microalgae and a cyanobacteria mixture on germinative activity, growth, and cannabinoid production in Cannabis sativa plants - Natalia Herrera; Tatiana C. Puentes-Escobar; Julian A. Álvarez-Pulido; Ronald Sanchez; Jelen Restrepo; Luis Fernando Echeverri (Journal of Applied Phycology, 2025)
The enhancement in agricultural productivity has been achieved through the application of pesticides and nutrients, mainly of synthetic origin. This practice has led to a dependence on the use of agrochemicals in order to obtain better results. However, the overuse application has created environmental and toxicological problems, so other alternatives are needed. For this reason, this study focused on evaluating the biostimulation of cannabis ( Cannabis sativa ) plants used in the production of cosmetics, pharmaceuticals, and phytotherapeutics through the application of three microalgae: Chlorella vulgaris , Ankistrodesmus falcatus , and Scenedesmus sp. and one cyanobacterium: Arthrospira platensis . This strategy aims to increase the cannabinoids production through a practical and environmentally friendly approach. In this way, crop quality can be improved while reducing fertilizers use, thus promoting more sustainable and efficient agricultural practices. Treatments combining nutrients and microalgae at different concentrations, a control in which only water was applied and a treatment containing only nutrients were used to assess seed germination, plant growth and the production of ten cannabinoids and other compounds present in the plants. The microalgae treatment alone stimulated germination processes in cannabis by 93%. The mixture of microalgae and cyanobacteria and the nutrients positively affected the growth of cannabis plants, increasing their length by up to 40% more than the control. Cannabinoid production was increased when the 50% nutrient mixture was used with the microalgae and cyanobacteria, resulting in increased production of five cannabinoids (CBD, Δ 9 -THC, CBDA, THCA, and Δ 8 -THC). These results demonstrate the potential of microalgae and cyanobacteria as sustainable biostimulants for cannabis cultivation. Graphical Abstract